Navigating Uncertain Terrain: Risk of Abuse or Misuse of Psychiatric Epistemic Power in the Face of Uncertainty Without Ethical Reflexivity and Regulation - Abdullah Yıldız; Berna Arda (Laws, 2025)
In this study, we examine the complex interplay between psychiatric epistemic power and its institutional applications through the phenomenon of “diagnosis removal” in Turkey. Within the constraints of limited mental health legislation, psychiatric diagnostic categories serve both as markers of risk and as administrative constructs that can be erased when convenient, presenting paradoxical challenges for healthcare providers and patients alike. Through a systematic analysis of case studies and theoretical frameworks, we explore how bureaucratic authorities can misuse psychiatric diagnoses in employment contexts. The study reveals a significant paradox where psychiatric expertise is simultaneously invoked and challenged, potentially undermining both therapeutic relationships and legal rights. This situation arises from a regulatory vacuum in mental health legislation, further exacerbated by a harm-based approach to mental health issues rather than a rights-based one. Key findings demonstrate how the institutional handling of psychiatric diagnoses creates a treatment disincentive effect, where individuals avoid seeking mental health care due to employment concerns. The analysis also reveals how concept creep and harm-based morality contribute to the misappropriation of psychiatric knowledge in administrative contexts. These findings highlight the urgent need for comprehensive mental health legislation that balances individual rights with public health concerns while protecting the integrity of psychiatric practice from institutional misuse, particularly in employment contexts.